2016
DOI: 10.3389/fneur.2016.00090
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Binocular Coordination during Sleep Deprivation

Abstract: To aid a clear and unified visual perception while tracking a moving target, both eyes must be coordinated, so the image of the target falls on approximately corresponding areas of the fovea of each eye. The movements of the two eyes are decoupled during sleep, suggesting a role of arousal in regulating binocular coordination. While the absence of visual input during sleep may also contribute to binocular decoupling, sleepiness is a state of reduced arousal that still allows for visual input, providing a conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Prior studies have shown that eyelid-closure/blink dynamics (e.g. Federal Highway Administration, 1998;Anderson et al 2013) and binocular gaze coordination (Horne, 1975;Tong et al 2016) are affected by fatigue or sleepiness, and that slow ocular drift accompanies the transition from wakefulness to sleep (Henn et al 1984;Santamaria and Chiappa, 1987;Ferrara et al 2000). Prior studies have also found altered saccadic eye movements associated with sleep deprivation.…”
Section: Relationship To Prior Literaturementioning
confidence: 99%
“…Prior studies have shown that eyelid-closure/blink dynamics (e.g. Federal Highway Administration, 1998;Anderson et al 2013) and binocular gaze coordination (Horne, 1975;Tong et al 2016) are affected by fatigue or sleepiness, and that slow ocular drift accompanies the transition from wakefulness to sleep (Henn et al 1984;Santamaria and Chiappa, 1987;Ferrara et al 2000). Prior studies have also found altered saccadic eye movements associated with sleep deprivation.…”
Section: Relationship To Prior Literaturementioning
confidence: 99%
“…Of note, sleep-deprived subjects in driving simulators have reduced peripheral attention (Jackson et al, 2008) and reduced ability to process peripheral signals (Rogé, Pébayle, El Hannachi, & Muzet, 2003). Gaze orientation, which reflects attention, is also affected by sleep deprivation, being less synchronised and slower (Tong et al, 2016). This is important because selective attention gives us the ability to focus on a particular part of the visual surround.…”
Section: Discussionmentioning
confidence: 99%
“…The oculomotor features, calculated from the eye tracking data, were aimed at characterizing visual-motor processing ( 33 ), motor control ( 34 ), and cognitive function ( 35 ). To evaluate visual-motor processing, metrics, such as reaction time of saccades in response to step changes in target position, velocity gains of smooth pursuit tracking, and the number of catch-up saccades that occurred during smooth pursuit were computed.…”
Section: Methodsmentioning
confidence: 99%